Hypoglycemic effect of Geranium ruizii Hieron. (pasuchaca) ethanolic extract on alloxan-induced hyperglycemia in rats. - Herrera Calderón, Oscar (2015)
Introduction: Geranium ruizii Hieron. (pasuchaca) is a medicinal plant used by traditional medicine to lower glycemia, in Ancash, Peru. Objective: To determine the hypoglycemic effect of Geranium ruizii ethanolic extract on alloxan-induced hyperglycemia in rats. Design: Experimental. Setting: Laboratorio de Farmacología Experimental, Facultad de Medicina Humana, Universidad San Marcos, Lima, Peru. Biological material: Geranium ruizii, eight weeks female Holtzman rats 200 ± 20 g of body weight. Interventions: Experimental hyperglycemia (>200 mg/dL) was induced with alloxan. Rats were divided into six groups of six rats each. Group I received 2 mL distilled water, groups II, III, IV received respectively Geranium ruizii 50, 150 and 300 mg/kg, group V glibenclamide 5 mg/kg and Group VI insulin 4IU/kg. Main outcome measures: Glycemic level (mg/dL), inhibition of DPPH (%), reduction of reactive species to barbituric acid (TBARS) (nmoles/mL), histopathology study. Results: G. ruizii at 150 mg/kg reduced hyperglycemia 68.58% at 2 h following alloxan induction (Kruskal Wallis; p< 0.001), reduced TBARS in vivo 22.34%, and inhibited DPPH 23.66% to 1.0 ug/mL; the pancreas tissue remained in good condition. Conclusion: The Geranium ruizii (pasuchaca) ethanolic extract showed hypoglycemic effect in alloxan-induced hyperglycemia in rats.